2015
DOI: 10.1111/jbl.12084
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐Based Logistics and Interfirm Team Processes: An Empirical Investigation

Abstract: P ractitioners are using performance-based logistics (PBL) strategies to reduce cost and improve value in industries such as defense, transportation, manufacturing, and healthcare. PBL is part of a group of increasingly popular buyer-supplier strategies that focuses on outcomes as oppose to the delivery of products or services. A key tenet of PBL is the use of innovation to create cost avoidance that benefits buyers and suppliers. In this research, we explore the interfirm team-level factors associated with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…The results empirically confirm that SCC increases the financial, operational and non-financial benefits of PBCs. Thus, we conclude that better SCC is critical to creating innovative investment in order to increase benefits by avoiding future costs in PBC (Randall et al, 2015). This finding is consistent with and provides empirical proof for the statements of Randall et al (2011), in which the authors emphasize the importance of this investment climate and relational exchange of suppliers for continuous value creation in PBC.…”
Section: Managerial Implicationssupporting
confidence: 86%
See 3 more Smart Citations
“…The results empirically confirm that SCC increases the financial, operational and non-financial benefits of PBCs. Thus, we conclude that better SCC is critical to creating innovative investment in order to increase benefits by avoiding future costs in PBC (Randall et al, 2015). This finding is consistent with and provides empirical proof for the statements of Randall et al (2011), in which the authors emphasize the importance of this investment climate and relational exchange of suppliers for continuous value creation in PBC.…”
Section: Managerial Implicationssupporting
confidence: 86%
“…This knowledge also includes technical expertise concerning the entire system, while a new knowledge source leads to innovation in the whole chain. In the study by Randall et al (2015), where the authors investigated inter-firm team-level factors associated with innovation in successful PBC, they found that Supply chain collaboration interdependent goals align with inter-firm relationships to create innovative investment solutions in PBC. Additionally, in their experimental study, Guajardo et al (2012) illustrated how product reliability is 25%-40% higher under PBC than under TBC.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the increasing practical relevance, the number of studies on PBC has increased recently (Selviaridis, 2011), but still surprisingly few academic publications have researched this subject (Buchanan and Klingner, 2007;Hypko et al, 2010;Selviaridis, 2011). In particular, there is a lack of empirical evidence (Holmbom et al, 2014), even if first empirical studies analyze PBC (Randall et al, 2014) or develop hypothesis from case studies or interviews for later empirical testing (Caldwell et al, 2009;Selviaridis and Norrman, 2014;Randall et al, 2015). At the same time, many authors stress on the uniqueness of each PBC, their situation and case-specific design and focus on the "one size does not fit all" of PBC (Hicks, 2012;Sols et al, 2007;Burkett, 2009;Geary and Vitasek, 2008).…”
Section: Introductionmentioning
confidence: 99%